Digital transformation in the halal industry: enhancing global trade competitiveness through an Islamic business ethics framework - Saragih, Eka Junila; Nia Zulinda; Ari Widiati; Vivi Sri Wahyuni (Universiti Teknologi MARA (UiTM), Malaysia, 2026)
This study explores the contribution of digital transformation to improving the competitiveness of the halal industry by integrating advanced technologies with Islamic business ethics. It examines the role of emerging technologies—such as blockchain, artificial intelligence (AI), the Internet of Things (IoT), and big data analytics—in enhancing transparency, operational efficiency, and accountability across the halal value chain, thereby strengthening consumer trust in product authenticity. Employing a qualitative research design based on a literature review, this study analyzes how digital technologies can reinforce halal industry competitiveness from an Islamic ethical perspective. The findings reveal that the digitalization of halal certification, through initiatives such as SIHALAL and SEHATI, streamlines the halal certification process, particularly for Micro, Small, and Medium Enterprises (MSMEs). Digital innovation not only expedites halal verification but also enhances product credibility and market value at the international level. Nevertheless, several challenges persist, including disparities in digital literacy, inadequate technological infrastructure, and limited public awareness regarding the reliability of online halal certification information. In addressing these challenges, the application of Islamic business ethics is essential. Ethical principles such as amanah (trustworthiness), ṣidq (honesty), and ʿadl (justice) should guide the implementation of digital technologies to ensure that digitalization promotes not only economic efficiency but also social equity and public welfare. Integrating Islamic values with digital innovation is expected to foster a competitive, inclusive, and sustainable global halal ecosystem, positioning the halal industry as a key driver of a just and value-based Shariah economy.